PLACE OF CHILDREN'S SPEECH DEVELOPMENT APPROACH SUGGOSTOPEDIK - Asqarova Kamola G‘ayratjon qizi (Zeta Repository, 2023)
In this article, using innovative technologies in the educational process and the development of speech the word about the activity the students will go. In this article, the main purpose of education speech activity of the recipients of the tool in the further development of the activity of some resources that can give you information on topics wide and deep so that they can work on improving your approach on this basis and from the use of methods and technologies that are necessary for suggostopediyali to get skills and qualifications to form relations.